HUBUNGAN ANTARA STRESS KERJA DENGAN BURNOUT PADA TENAGA MEDIS - Anisa Dwi Abelia (Surabaya Biomedical Journal, 2026)
Background: Burnout is a common psychosocial issue experienced by healthcare workers due to chronic occupational stress. Unmanaged work stress can negatively impact healthcare quality and the well-being of medical personnel. Objective: To examine the relationship between occupational stress and burnout among healthcare workers based on recent literature. Methods: This study employed a descriptive literature review design. Articles were selected from Scimago and SINTA databases, limited to publications from 2020–2025. A total of 16 relevant articles were analyzed. Results: Most articles indicated a significant relationship between occupational stress and burnout. Contributing factors include excessive workload, role conflict, lack of organizational support, and night shifts. Conclusion: Occupational stress is significantly associated with burnout among healthcare workers. Effective stress management is essential to prevent burnout and enhance the quality of healthcare services.